Multifocal cutaneous epithelioid hemangiodothelioma on the same lower limb - Khallaayoune, Mehdi; Azzahra Elgaitibi, Fatima; Meziane, Mariame; Ismaili, Nadia; Benzekri, Laila; Senouci, Karima (International Journal of Research in Dermatology, 2021)
Epithelioid hemangioendothelioma (EHE) is a rare low-grade vascular tumour mainly affecting bones, deep soft tissues and exceptionally the skin. Multifocal cutaneous involvement is uncommon and should raise suspicion for metastasizing extracutaneous epithelioid hemangiodothelioma. Hereby we report the case of a young patient with multifocal cutaneous EHE involving the same lower limb. We emphasize the necessity for dermatologists to evoke the diagnosis of EHE in patients presenting with nonspecific tumours of the extremities. Prompt management and diagnosis are essential in this potential aggressive tumour.